Biographie von Wolfgang Amadeus Mozart - Bürkli, Johann Georg 1793-1851; Flies, Bernhard 1770-1851 (Zürich Allgemeine Musikgesellschaft, 1832)
In the 17th century music in Zürich was dominated by three collegia musica: the first was ‘zum Chorherrensaal’, followed by the ‘ab dem Musiksaal’ (from 1613) and ‘zur deutschen Schule’ (from 1679). Initially they were concerned only with sacred music, but later also performed contemporary German and Italian secular music. The three societies merged in 1812 to form the Allgemeine Musikgesellschaft Zürich (AMGZ), which since 1813 has produced books on musical subjects in a series of ‘Neujahrsblättern’, the successors to a series of New Year collections of polyphonic pieces published by two of the collegia musica from 1685 and 1713 respectively.
Volume 1 contains a lithograph with an imaginary meeting of Mozart (at Count Firmian's house in Milan, where he received a Metastasio edition?) and a portrait of the composer engraved by R. Rahn -- Volume 2 contains the famous illustration of Mozart attending a performing of 'Die Enftührung aus dem Serail' in Berlin, 1789, next to a 'Verzeichniß sämmtlicher Werke von Wolfgang Amadeus Mozart', and the lullaby (by Bernhard Flies, but falsely ascribed to Mozart) 'Schlafe, mein Prinzchen, schlaf ein' KV 350
See 04J20, 04J21, 10B20, 11H13, 26D03 and G1-028 for similar collections
Acquired by Ton Koopman from EOS Buchantiquariat Benz, Zürich
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Allgemeine Musikgesellschaft Zürich (Switzerland); 18th Century (1701-1800); 19th Century (1801-1900); Composer; Biography; Iconography; Austria; Zürich (Switzerland)